PENERAPAN MODEL KEPEMIMPINAN TRANSFORMASIONAL DALAM DUNIA PENDIDIKAN - Zainal Berlian (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
Leadership is an important discussion, especially in order to improve thequality of education, because in the world of education can not be separatedfrom the influence of education, especially related to the formation ofeducational policy. One model that is quite popular in the worldof education is transformational leadership. A leader in education should beable to apply the model of transformational leadership. Therefore,transformational leadership is not only based on the need for self-esteem,but also to improve awareness of a leader to act best in accordance with the studyof management development and leadership that sees humans,performances, and growth as a side affects one to another. This Leadership is oriented toward the change of vision that is the leader's ability to create, define, communicate, socialize,transform, and implement the ideal thoughts coming from himself or as aresult of social interaction among members of the organization and itsstakeholders are believed to be the ideals of the organization in the futurethat must be achieved or realized through the commitment of all personnel.